2005
DOI: 10.1161/01.hyp.0000175474.99326.bf
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin-4 Receptor–Deficient Mice Are Not Hypertensive or Salt-Sensitive Despite Obesity, Hyperinsulinemia, and Hyperleptinemia

Abstract: Abstract-The purpose of this study was to test whether the melanocortin-4 receptor (MC4R) is critical in the development of hypertension associated with obesity and its metabolic disorders. MC4R-deficient homozygous (Ϫ/Ϫ) and heterozygous (ϩ/Ϫ) and wild-type (WT) C57BL/6J mice 17 to 19 weeks old (nϭ5 to 7 per group) were implanted with telemetry devices for monitoring 24-hour mean arterial pressure (MAP) and heart rate (HR). After 3-day stable control measurements on normal-salt diet (NSD; 0.4% NaCl), mice rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
95
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 40 publications
12
95
0
Order By: Relevance
“…Chronic pharmacologic blockade of MC3R and MC4R causes weight gain and a reduction in heart rate but no increase in arterial pressure. Mc4r-null mice maintain normal blood pressure despite marked obesity and are unresponsive to the pressor effects of central α-MSH administration (64). We have shown that both increases and decreases in central melanocortin signaling influence blood pressure in humans and that the effects are not explained by changes in circulating insulin levels or insulin sensitivity (65).…”
Section: Mutations That Disrupt Melanocortin Signalingmentioning
confidence: 80%
“…Chronic pharmacologic blockade of MC3R and MC4R causes weight gain and a reduction in heart rate but no increase in arterial pressure. Mc4r-null mice maintain normal blood pressure despite marked obesity and are unresponsive to the pressor effects of central α-MSH administration (64). We have shown that both increases and decreases in central melanocortin signaling influence blood pressure in humans and that the effects are not explained by changes in circulating insulin levels or insulin sensitivity (65).…”
Section: Mutations That Disrupt Melanocortin Signalingmentioning
confidence: 80%
“…Conversely, blockade of CNS MC3/4Rs in rodents causes voracious feeding and rapid weight gain and reduces rather than increases BP (31). Similarly, mice with MC4R deficiency are hyperphagic and obese and have many features of the metabolic syndrome but are not hypertensive on normal or high salt diets (32).…”
Section: Chronic Activation Of the Cns Pomc-mc3/4r Pathway Causes Snsmentioning
confidence: 99%
“…The hyperinsulinemia in this model is partially independent of obesity, as young MC4-R-deficient animals have been shown to have elevated circulating insulin levels prior to the onset of obesity (Fan et al, 2000). Despite their profound obesity in adulthood, the MC4-R-deficient animals are not hypertensive, but tend to be hypotensive (Tallam et al, 2005). Finally, another notable feature of the MC4-R null mouse is a profound sensitivity to high-fat feeding, which exacerbates the hyperphagia, obesity and hyperinsulinemia (Sutton et al, 2006).…”
Section: Melanocortin 4 Receptor (Mc4-r) Null Mousementioning
confidence: 99%